Enhancing the evidence-based healthcare principles in clinical practice guidelines development in the Czech Republic: a best practice implementation project. (September 2022) - Vrbová, Tereza; Klugarová, Jitka; Pokorná, Andrea; Dušek, Ladislav; Líčeník, Radim; Klugar, Miloslav
ABSTRACT: Objectives: The main aim of this project was to enhance compliance with the best available evidence in clinical practice guidelines (CPGs) development based on evidence-based healthcare (EBHC) and GRADE (grading of recommendations, assessment, development and evaluation) principles in healthcare professionals and healthcare providers. Introduction: In various healthcare fields, the quality of care provided in different healthcare settings may vary. Guidelines following the EBHC principles should help make the right decisions in healthcare by providing the best healthcare option and be available for all patients. The perspectives of all engaged stakeholders should be respected, however. Within the Czech Republic, there had been no standardized process of CPG development. Methods: A baseline audit was conducted to demonstrate the status quo of the EBHC in the Czech Republic, which identified several barriers. Consequently, strategies (educational activities, methodological guidelines) to overcome the barriers were suggested and implemented. Two more audits followed (November 2017, November 2020). Results: The baseline audit results showed no or very low compliance to the best available evidence in CPG development. After the implementation, an increased compliance in all audit criteria (national methodology guidelines, trustworthy CPGs, experienced methodologists, clinical summaries) has been reported. The project has helped to establish procedures of CPGs development, enhanced knowledge and skills on EBHC in healthcare professionals, and ignited patients' involvement in CPG development. Conclusions: The implementation project showed an increasing number of national methodology guidelines, CPGs being developed using EBHC and GRADE principles and HC professionals educated in EBHC. A national center for CPGs development within the Ministry of Health is being planned to sustain the project achievements.